Combining space syntax and location - based methods to map urban accessibility :Powerpoint - Flacke, J. (University of Twente, 2020)
This lecture presents: Alternative to map access to jobs; Location based accessibility; Space Syntax results ; Access to jobs as a function of distance decay and geometric accessibility; Integrated maps ; The macro_ssx model and land value trends; Land value models.